Дієслова-синоніми на позначення внутрішнього стану людини у художніх текстах І. Нечуя-Левицького - Мялковська, Людмила; Myalkovska, Ljudmyla (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано зафіксовані у художніх творах І. Нечуя-Левицького дієслова-синоніми на позначення внутрішнього, психологічного стану людини; виявлено, що такі слова у досліджуваних текстах формують розгорнений синонімічний ряд. The article analyzes reported in works of art I.Nechuy-Levitsky’s verb synonyms to describe internal psychological state of man, found that the words in the studied texts form the synonymic series deployed. The characteristic trait of the individual style of the writer use in the study ranks synonymous phraseology. Determined that the verb to describe the internal state of the person contributing to diversification of artistic prose text, including that which has the nature of narrative style.
Verbs Synonyms that Mean the Internal State of Man in Texts I. Nechui-Levytskyi’s
Keywords: лексика; загальномовний словник; мовотворчість І. Нечуя- Левицького; лексико-семантична група; синонімічний ряд, дієслова-синоніми; vocabulary; general language dictionary; linguistic creativity I. Nechuy-Levitsky’s; lexical-semantic group; synonymous number; verbs; synonyms